Individualized Pastureland Use: Responses of Herders to Institutional Arrangements in Pastoral China (2013)
This paper analyzes increasingly individualized herding behavior after the implementation of a grazing ban policy in northern China based on empirical research in 12 pastoralist villages. The findings reveal that de-collectivization of pastureland has not necessarily led to direct changes in individual land use strategies. Instead, a wider institutional context influenced by the implementation of a grazing ban has led to more individualized herding and increased short-term considerations of profit maximization in the study area, both of which are seen to undermine the sustainable use of pastureland. Based on our observations of herder responses to privatization, the grazing ban and a short experiment with lifting the grazing ban, we propose that the special characteristics of grassland and pastoralism call for institutions that facilitate locally originated pasture land use practice (e.g., co-operative herding, self-organized management) instead of exclusive reliance on a rigidly defined private property regime focused on fixed property boundaries.